Grinding Kinetic Equation with an Arbitrary Law of Waiting Time Distribution - L. V. Korolev; D. O. Bytev (Моделирование и анализ информационных систем, 2012)
A generalized kinetic equation of a grinding process is obtained. The equation is valid for arbitrary distribution of particle destruction waiting time. In terms of the equation a grinding process model with the power law of waiting time distribution is proposed. The particle size dependence of the power index is taken into account and its in°uence on grinding process kinetics is investigated.